Management of Multidrug-Resistant Gram-Negative Meningitis in Post-Operative Neurosurgical Patients: A Case Series - Kaur, Ruchinder; Jain, Varun; Gupta, Rahul; Singh, Swati (Journal of Nepalese Society of Critical Care Medicine, 2026)
Bacterial meningitis is a serious complication following neurosurgical procedures, particularly when foreign materials such as external ventricular drains, lumbar drains, or ventriculo-peritoneal shunts are used. In recent years, there has been an increase in cases caused by multidrug resistant Acinetobacter baumannii. We retrospectively reviewed cases from January 2022 to January 2024 at our institute and identified three cases of Acinetobacter meningitis amongst other gram-negative meningitis that occurred post neurosurgical procedures in which we had given antibiotics through intrathecal/intraventricular route along with intravenous route. One patient had undergone trans-nasal trans sphenoidal endoscopic resection of pituitary tumour and the other two patients had decompressive craniectomy for brain hemorrhage. All patients were initially treated with intravenous polymyxins and other antibiotics. Due to limited response, intrathecal and intraventricular routes were employed for antibiotic administration which resulted in successful cerebrospinal fluid sterilization. Amongst three patients, two patients improved and one succumbed to complications. Our experience suggests that intrathecal or intraventricular administration of colistin can be used in managing multidrug resistant Acinetobacter baumannii meningitis which gets refractory to intravenous antibiotics.